2022
DOI: 10.46690/capi.2022.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of the water bridge in organic shale nanopores: A molecular dynamic study

Abstract: In the last decades, shale gas development has relieved the global energy crisis and slowed global warming problems. The water bridge plays an important role in the process of shale gas diffusion, but the stability of the water bridge in the shale nanochannel has not been revealed. In this work, the molecular dynamics method is applied to study the interaction between shale gas and water bridge, and the stability can be tested accordingly. CO 2 can diffuse into the liquid H 2 O phase, but CH 4 only diffuses at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
3
5
0
Order By: Relevance
“…The main component of shale gas is CH 4 , and shale gas is a mixture that always contains an amount of moisture. The moisture is generated by the gas migration and the thermal reaction of organic matter. The content of moisture affects the development of shale gas, and the adsorption capacity of shale gas is inhibited by more moisture content. , In the past few years, carbon capture, utilization, and storage (CCUS) have been regarded as a direct way to reduce carbon pollution and slow global warming . The adsorption and diffusion processes of CH 4 and CO 2 in coal matrixes, which are similar to those of kerogen structures, were studied, , and the properties of organic matrixes will be affected by H 2 O and CO 2 . , The competitive adsorption of CH 4 and CO 2 was also studied in nanoconfined slits .…”
Section: Introductionmentioning
confidence: 99%
“…The main component of shale gas is CH 4 , and shale gas is a mixture that always contains an amount of moisture. The moisture is generated by the gas migration and the thermal reaction of organic matter. The content of moisture affects the development of shale gas, and the adsorption capacity of shale gas is inhibited by more moisture content. , In the past few years, carbon capture, utilization, and storage (CCUS) have been regarded as a direct way to reduce carbon pollution and slow global warming . The adsorption and diffusion processes of CH 4 and CO 2 in coal matrixes, which are similar to those of kerogen structures, were studied, , and the properties of organic matrixes will be affected by H 2 O and CO 2 . , The competitive adsorption of CH 4 and CO 2 was also studied in nanoconfined slits .…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have already conducted studies on pore characterization in different shales, in which it has been found that shale pore networks are dominated by organoporosity. ,,, Consequently, we use intraparticle organic pores to illustrate why weakly deformed shales are mesopore-rich with low permeability and strongly deformed shales are macropore- and fracture pore-rich with high permeability, as shown in Figure . We assume that the micropores, mesopores, and macropores of the primary structural shale are all developed in a certain proportion and scale.…”
Section: Resultsmentioning
confidence: 99%
“…Kerogen is an essential part of the organic matter not soluble in common polar solvents. , The general consensus has been that kerogen is mainly hydrophobic; however, recent studies have observed that the presence of heteroatoms (polar nitrogen-, sulfur-, and oxygen-containing (NSO) compounds) in kerogen might induce a mixed-wet or even hydrophilic characteristics in kerogen, leading to an intricate wetting behavior of this matter. Thus, obtaining an accurate knowledge of kerogen wettability and gaining better insight into how kerogen impacts fluid flow can profoundly help not only in production from unconventional shale but also in effective geological carbon sequestration (GCS) since shale reservoirs have shown promising results to act as CO 2 sinks. CO 2 can be stored in shale reservoirs through the residual or capillary trapping mechanism, by which carbon is trapped through high capillary forces in the porous media of the formation rock. , …”
Section: Introductionmentioning
confidence: 99%